Sociomoral Reasoning, Empathy, and Meeting Developmental Tasks During the Transition to Adulthood in Autism Spectrum Disorder. - Senland, Amie; Higgins-D'Alessandro, Ann (Journal of Autism & Developmental Disorders, 2016)
This mixed methods study investigated sociomoral reasoning, empathy, and challenging and supportive factors during the transition to adulthood in emerging adults (18-27-years-old) with autism spectrum disorder (ASD) to better understand how these variables facilitated positive developmental outcomes. Same-aged ASD ( n = 22) and typically developing (TD) ( n = 22) groups completed quantitative and qualitative measures assessing these constructs. Compared to the TD group, the ASD group had significantly lower sociomoral reasoning and perspective-taking, significantly higher personal distress, but similar empathic concern. Inductive content analysis showed those with ASD and better developmental outcomes more often discussed the value of informal social support and utilized perspective-taking during challenging sociomoral situations.